Religion as a Natural Kind: The Biological and Semantic Search for a Definition - Johnson, Jeffery L. (Philosophy & theology, 2015)
Anthropologists tell us that every known culture has had something that we would recognize as religion, and that this has been true for at least 50,000 years. The best explanation for this is a genetic predisposition for religious sympathy and practice, hard-wired into the human brain by the forces of natural selection; it is part of our basic human nature. We can therefore treat religion as a natural kind--similar to gold or water--and attempt to articulate this neurobiological essence in everyday language. Such an articulation would yield an empirically driven definition of religion.